2017
DOI: 10.3390/su9040525
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of Sustainable Rural Tourism in the United Kingdom of Great Britain and Northern Ireland (UK): Comparative Study of β and σ Convergence in the Economic Development Regions

Abstract: Abstract:Tourism is an activity which globally develops proportionally with the evolution of progress. The opportunities we enjoy are bigger than ever, but their price should be lowered in order for the global society to develop its wealth. This can be performed by sustainability, a concept which will join in the future all economic activities, not only tourism. Our analysis is focused on the specific case of the UK, one of the main tourist destinations in the world. It is well known that cultural tourism is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…It made up 9.8% of global Gross Domestic Product (GDP) and contributed to the global economy with $7.61 trillion USD in 2016 [1]. The analysis of the World Travel and Tourism Council (WTTC), which included 184 countries, has shown that the tourism sector generated 284 million workplaces, meaning that 1 out of 11 workplaces in the world comes from the tourism sector [2]. The ways in which its development affects other sectors (such as forestry, food processing, agriculture, livestock raising, fishing, and handicrafts) can improve the entire community's well-being [3].…”
Section: Introductionmentioning
confidence: 99%
“…It made up 9.8% of global Gross Domestic Product (GDP) and contributed to the global economy with $7.61 trillion USD in 2016 [1]. The analysis of the World Travel and Tourism Council (WTTC), which included 184 countries, has shown that the tourism sector generated 284 million workplaces, meaning that 1 out of 11 workplaces in the world comes from the tourism sector [2]. The ways in which its development affects other sectors (such as forestry, food processing, agriculture, livestock raising, fishing, and handicrafts) can improve the entire community's well-being [3].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the modern tourist is oriented to focus on themes geared towards more sustainable urban behaviour [5], management of natural and environmental resources [6][7][8], rediscovery of rural areas [9][10][11][12] and, generally, environmental protection. This attitude is also evident when mountain areas are taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Convergence was initially analysed in Solow's studies in 1956 who defines it as a natural process based exclusively on market functionality (Solow, 1956 modified and developed to explain the differences among countries, and the modality of their reduction according to factors like saving rate, population growth rate, labour mobility, migration, etc. Butnaru and Haller (2017) study the impact of sustainable rural tourism on the economy of the development regions of UK and Northern Ireland by using the method of σ and β convergence. In this case it was demonstrated, by analysing GDPT, that the convergence process performed slowly, and sustainable rural tourism influenced the development.…”
Section: Analysis Of Economic Growth In Tourism Under the Impact Of Tmentioning
confidence: 99%